Legal Protection For MSMES In West Seram Regency During The Pandemic Period - Ronald Fadly Sopamena; Adonia Ivonne Laturette; Marselo Valentino Geovani Pariela (Unram Law Review, 2022)
The study aims to examine legal protection for MSMEs during the Covid-19 Pandemic in West Seram Regency.The type of this research is socio-legal research, which is a combination method between doctrinal legal research and empirical legal research. The results of the study found that the form of legal protection that the West Seram Regency Government could provide to MSMEs, one of which was by issuing a policy of aiding MSMEs who are affected by the pandemic, whether MSMEs were unable to pay installments or were losing money during the pandemic or for MSME actors even though they did not have debt. in the form of Business Assistance, it is worth of Rp. 1,200,000 which provided twice in a year in purpose to assist the business. However, there are challenges in the policy implementations due to not all MSME owners are able to receive this assistance.